Evaluasi Sifat Alir Dari Pati Talas Safira (Colocasia esculenta var Antiquorum) Sebagai Eksipien Dalam Formulasi Tablet - Resky Khairunnisa , Michrun Nisa, Radhia Riski , Aisyah Fatmawaty (STIFA Makassar, 2016)
The flow properties of the active substance and additives is very important to be known for the manufacture of a good tablet . Fluid powder or starch good for felted very important to ensure homogeneous mixing and uniformity of weight are acceptable for tablets felts . The purpose of this study was to determine whether the evaluation of the characteristics of the flow properties of the starch taro safira in accordance with the parameters of good flow properties . The evaluation includes an evaluation of the results obtained water content 7.20% , 4.72 starch pH test , the test angle of repose 21.433 , 1.19 moisture content test , test flow rate of 2,242 g / sec , the real gravity of 97.1131 g / mL , the specific gravity of the incompressible 97.787 g / mL , kompersibilitas 0.629 % , 97.1131 % porosity and surface shape inspection of the starch granules using SEM (Scanning Electron Microscope ).